Historical dictionary of Jesus - Harrington, Daniel J. (Lanham, Md. : Scarecrow Press, 2010)
Jesus of Nazareth is arguably the most famous and influential human being who has ever lived on earth. In the Historical Dictionary of Jesus, author Daniel J. Harrington delves into the ancient literary sources about Jesus, modern methods of approaching these sources, the major events in Jesus' life, persons and places associated with him, the form and content of his teachings, what can be said about his death and the claim that he was raised from the dead, and the contributions of major modern scholars to the quest of the historical Jesus. The book consists of three parts: an introduction to.
Preface; Abbreviations of Biblical Books; Introduction; The Dictionary; Bibliography; About the Author.
Includes bibliographical references (pages 177-189).
Print version record.
Master record variable field(s) change: 082
Keywords: Jesus Christ -- Dictionaries; Jesus Christ; Dictionaries; Jesus Christ; Religion; RELIGION -- Christian Theology -- Christology; Electronic books; Dictionaries